2018
DOI: 10.1155/2018/6428630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylcysteine on Dyslipidemia and Carbohydrate Metabolism in STZ-Induced Diabetic Rats

Abstract: Background Type 1 diabetes mellitus (T1DM) is characterized by insulin-deficient production leading to hyperglycemia, which is associated with diabetic complications such as cardiovascular diseases. Antioxidants have been proving a good alternative to diabetic complications, with N-acetylcysteine (NAC) having antioxidant characteristics. The aim of this study was to assess the effect of NAC on the lipid profile and the atherogenic index (AI) in streptozotocin- (STZ-) induced diabetic rats. Method 32 male Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The co-administration of NAC revealed partial recovery of lipid pro le as evidenced by normalization of total cholesterol, triglycerides, HDL-cholesterol and atherogenic index and decrement of LDL-cholesterol con rming the improvement of dyslipidemia, which is supported by previous studies [21,50,51]. The lipid-lowering action of NAC in our MS animal model of hyperlipidemia can be partially ascribed to the suppression of mRNA expression of lipogenic related enzymes [52].…”
Section: Discussionsupporting
confidence: 84%
“…The co-administration of NAC revealed partial recovery of lipid pro le as evidenced by normalization of total cholesterol, triglycerides, HDL-cholesterol and atherogenic index and decrement of LDL-cholesterol con rming the improvement of dyslipidemia, which is supported by previous studies [21,50,51]. The lipid-lowering action of NAC in our MS animal model of hyperlipidemia can be partially ascribed to the suppression of mRNA expression of lipogenic related enzymes [52].…”
Section: Discussionsupporting
confidence: 84%
“…Diabetic hyperlipidemia can be regarded for promoting cardiovascular diseases and the management of diabetic dyslepidemia is a key factor in treating diabetes (Kaga et al, 2018). The significant elevation of Triglycerides (TGs), LDL-C and total cholesterol in diabetic rats (group II) in the present study was similar to what was reported previously (Ahmadvand et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that NAC may inhibit hepatic steatosis and development of glucose intolerance and improve lipid profiles [ 65 , 66 ]. In type 2 diabetic humans, there does not appear to be any benefit in improving glucose tolerance or ß -cell function with the addition of NAC in short-term trials (2 weeks) [ 67 ].…”
Section: Metabolic Syndrome Including Nonalcoholic Fatty Liver Disease Diabetes and Polycystic Ovarymentioning
confidence: 99%